Mutagenic activity and metabolites in the urine of workers exposed to trinitrotoluene (TNT). - Ahlborg, G (1988)
Urine samples taken after work and after a free weekend from 50 workers employed in various activities in a chemical plant manufacturing explosives were analysed. On the basis of hygienic surveys, the subjects were divided into three categories of exposure to trinitrotoluene (TNT). The urine analyses consisted of gas chromatographic identification of TNT and its two metabolites, 4-ADNT and 2-ADNT, and a determination of the mutagenic activity. Two frame shift detector strains of Salmonella typhimurium were used, TA 98 and TA 98 NR, the latter being deficient in endogenous nitroreductase activity. On the basis of previous results on TNT mutagenicity, no exogeneous metabolic system was used to test the urine concentrates. Both tester strains showed that the mean urinary mutagenic activity was higher in the after work samples than in post weekend samples from the same subjects, showing that bacterial nitroreductase activity was not significantly responsible for the mutagenicity, although the response was higher with strain TA 98 than with TA 98 NR. The interindividual variation in urine mutagenicity was high, however, and the difference between the two sampling times was statistically significant (p less than 0.05) only for the high exposed group (workers in trotyl foundry and sieve house). Correlation between urinary mutagenicity and concentration of TNT in urine was poor; correlation was significant only with the urinary concentration of 4-ADNT. The correlation between urinary TNT and both metabolites was good (p less than 0.001). These results suggest that analysis of 4-ADNT in urine would be a sufficient biological measure for controlling exposure to TNT.